Translational models of cannabinoid vapor exposure in laboratory animals. Issue 2 (28th October 2021) - Moore, Catherine F.; Stiltner, Jeffrey W.; Davis, Catherine M.; Weerts, Elise M.
Abstract : Cannabis is one of the most frequently used psychoactive substances in the world. The most common route of administration for cannabis and cannabinoid constituents such as Δ-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) is via smoking or vapor inhalation. Preclinical vapor models have been developed, although the vaporization devices and delivery methods vary widely across laboratories. This review examines the emerging field of preclinical vapor models with a focus on cannabinoid exposure in order to (1) summarize vapor exposure parameters and other methodological details across studies; (2) discuss the pharmacological and behavioral effects produced by exposure to vaporized cannabinoids; and (3) compare behavioral effects of cannabinoid vapor administration with those of other routes of administration. This review will serve as a guide for past and current vapor delivery methods in animals, synergize findings across studies, and propose future directions for this area of research.